On Biorthogonalization of a Dirichlet System Over a Finite Interval - Martirosyan, Mher; Martirosyan, Davit (Armenian Journal of Mathematics, 2022)
Ultimately aiming to estimate Dirichlet polynomials, a representation problem for special biorthogonal systems of exponentials is explored in $L^2(0,a)$. If $a=+∞$, a method of construction of such systems through suitable Blaschke products is known, but the method ceases to operate when $a$ is finite.It turns out that the Blaschke product cannot be even adjusted to maintain the old method for the new situation. The biorthogonal system is then represented by a single determinant of a modified Gram matrix of the original system. Bernstein-type inequalities for Dirichlet polynomials and their higher order derivatives are established. The best constants and extremal polynomials are obtained in terms of the Gram matrix.